Electrocardiographic modifications induced by breast implants. Issue 5 (28th March 2019) - Bun, Sok‐Sithikun; Taghji, Philippe; Errahmouni, Abdelkarim; Laţcu, Decebal Gabriel; Al Amoura, Alaa; Enache, Bogdan; Hugues, Thomas; Yaïci, Khelil; Saoudi, Nadir
Abstract : Background: Echocardiography realization can be challenging in the presence of breasts implants (BI). It is less known if electrocardiograms (ECG) may be modified in the presence of BI. Methods: ECG from women with BI (and without any known cardiac structural disease) were sent and analyzed by two experienced electrophysiologists (EP1 and EP2) who were blinded and completely unaware of the context of the patients (Group 1). ECG from a control matched‐group of female women without BI (Group 2) were also blindly sent for analysis. Results: ECG were collected from 28 women with BI (42 ± 8 years) without any acute medical condition. A proportion of 42% of the ECG were considered abnormal by EP1 and 46% by EP2. The abnormalities were for EP1: negative T waves (5), ST depression in inferolateral leads (2), absence of R wave progression from V1 to V4 (4), left ventricular (LV) hypertrophy (1), long QT(1), early repolarization (1), short PR (1); For EP2: negative T waves (6), ST depression in inferolateral leads (2), absence of R wave progression from V1 to V4 (4), LV hypertrophy(3), long QT (1), early repolarization (1). ECG from group 2 were considered abnormal in only 1 patient (5%) for EP1, and normal in all for EP2 ( P  = 0.0002 between the groups). Conclusions: ECG from women with BI were considered abnormal in 42% to 46% of the cases by expert readers. ECG interpretation can thus be misleading in these women.